Corrosion of glass, ceramics, and ceramic superconductors : principles, testing, characterization and applications - Clark, David E.; Zoitos, Bruce K. (Materials science and process technology series. Ceramic and other materials--processing and technology., 1992)
Presents fundamental chemical reactions, equations, computer codes and models, and examples by professionals in the field. Contents: Biomaterials, Optical Components, Construction, Materials, Nuclear Waste Containment, Ceramic, Superconductors, and Archeologically Significant Articles.